Photoinduced superconducting nanowires in GdBa2Cu3O6.5 films - Decca, R.S. (1998)
Fil: Maiorov, B. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina